A relação memória-linguagem nas demências: abrindo a caixa de Pandora - Galli, Juliana F. Marcolino (2013)
The issues that drove this work arise in the attendance of individuals with a medical diagnosis of early-stage dementia. Invariably, these patients complained of memory difficulties. However, they were little affected by their repetitive speech and did not hold a demand for care. Other issues on the inclusion of the family and the direction of the monitoring of those cases arose. From the theoretical point of view, this paper discusses the language-memory relationship in dementia. From a clinical perspective, the hearing of complaints of memory difficulties in a so-called Language Clinic is questioned. The starting point is presenting state of the art in medical and phonoaudiological clinics in dementia. The present discourse is guided by the Cognitive Neuropsychology, which refers to the understanding of memory as storing and language as expression of such content. The next theoretical step moves away from these neuropsychological studies and goes toward psychoanalysis, more specifically to the route of Freud in the foundation of the Unconscious and the developments that Lacan points out with the significant theory. Theoretical trajectory that touches the relation perception-object. The relation language-memory was investigated under the assumption that the subject is effect of language and that also memory is effect of language. Assumptions that are consistent with reflections submitted by the researchers of the research group "Acquisition, Pathology and Language Clinic", coordinated by Lier-DeVitto and Arantes at LAEL / DERDIC. Finally, the clinical questions were mobilized by the reading operators constructed throughout the chapters